Problem Management in Worker Assistance Systems Problemmanagement in Werker-Assistenz-Systemen Entwicklung einer softwaregeführten Problemlösung für die Prototypenmontage - Rupp, Stephan; Müller, Rainer; Kerker, Sebastian; Faltus, Florian; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2020)
Development of a software-guided problem solving tool for the assembly of prototypes. Thanks to virtual planning methods and tools the first drafts of series-production assembly processes are already available in early stages of vehicle development. This allows for the use of assembly assistance systems for the process validation during the assembly of prototypes similar to the systems that are already commonly used in series production. However, as the process maturity in this early development stage is low and the process is continuously evolving, such systems need to be capable of handling problems and frequent changes. For this purpose, a problem reporting process has been developed and integrated into an assistance system to guarantee an efficient know-how transfer from the assembly of prototypes to development departments and thus to series-production.
CRIS-Team Scopus Importer:2023-03-07